Pseudoporpoloma, a new genus for Agaricus pes-caprae (Agaricales, Tricholomataceae) - Vizzini, Alfredo; Consiglio, Giovanni; Ercole, Enrico; Setti, Ledo (Phytotaxa, 2016)
Pseudoporpoloma (Agaricales) is a new monospecific genus established for Agaricus pes-caprae, a grassland species previously placed in Tricholoma or Porpoloma. Pseudoporpoloma is morphologically distinguished by a Tricholoma-like habit, a conical radially fibrillose pileus, and amyloid spores. Phylogenetic analyses based on a combined ITS-LSU-rpb2 sequence dataset place Pseudoporpoloma close to Pseudotricholoma and Tricholoma.